THE IMPORTANCE OF DIGITAL MARKETING STRATEGIES IN THE SOCIETY 5.0 ERA FOR MSMES IN JAMBI CITY - Trilakshmi, Nasta (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the importance of digital marketing strategies for MSMEs in Jambi City in facing the challenges of the Society 5.0 era through a literature review approach with a focus on market expansion, promotion cost efficiency, and increased profitability. With a significant MSME population in Jambi City as part of more than 99% of the total national business units, digital transformation has become a strategic imperative for MSMEs to increase competitiveness and achieve sustainable growth. The analysis shows that the adoption of digital marketing has a positive correlation with the performance of MSMEs, where behavioral control factors and subjective norms have a significant effect on the intention of using digital platforms. The structured digital transformation program in Jambi City showed high effectiveness with 80% of participants successfully registering for independent NIB, 88% routinely recording digital finances, and 75% actively creating promotional content. The use of social media and digital platforms allows MSMEs to reach a wider market by reducing promotional costs by up to 70% compared to conventional methods, while increasing profit potential through the expansion of consumer segmentation. However, limited capital, human resources, and technological infrastructure are still major obstacles. A sustainable innovation strategy that integrates local wisdom with digital technology has been proven to increase the competitive advantage of MSMEs and provide a significant return on investment. Recommendations include the development of holistic capacity building, access to technology financing, and the creation of a supportive digital ecosystem for the transformation of MSMEs towards Society 5.0 that prioritizes sustainable profitability.